High performance alternating polymers based on two-dimensional conjugated benzo[1, 2-b:4, 5-b′]dithiophene and fluorinated dithienylbenzothiadiazole for solar cells. Issue 81 (16th August 2016) - Cong, Zhiyuan; Liu, Shuo; Zhao, Baofeng; Wang, Weiping; Liu, Hongli; Su, Jin; Guo, Zhaoqi; Wei, Wei; Gao, Chao; An, Zhongwei
Abstract : Three D–A polymers based on alkylthienyl substituted benzo[1, 2- b :4, 5- b ′]dithiophene (BDTT) and fluorinated 4, 7-dialkylthienyl-2, 1, 3-benzothiadiazole (DTBT) derivatives were synthesized and applied as donors in BHJ solar cells. Abstract : Three donor–acceptor polymers based on two-dimensional conjugated alkylthienyl substituted benzo[1, 2- b :4, 5- b ′]dithiophene (BDTT) and fluorinated 4, 7-dialkylthienyl-2, 1, 3-benzothiadiazole (DTBT) derivatives were synthesized and applied as donor materials for bulk heterojunction solar cells. The effects of fluorine substitution on the absorption properties, energy levels, dielectric constants and photovoltaic properties of the polymers were investigated. We found that the incorporation of fluorine atoms on the DTBT unit can effectively deepen the highest occupied molecular orbital (HOMO) energy level and increase the dielectric constant of the polymers. As a result of these improved properties, a high open-circuit voltage ( V oc ) of 0.85 V was obtained for the optimal conventional polymer solar cells (PSCs) based on a two-fluorine-substituted analogue P3 blended with [6, 6]-phenyl-C71 butyric acid methyl ester (PC71 BM) as the active layer (1 : 1.5), giving rise to a high power conversion efficiency (PCE) of 7.48%. The influences of the molecular weight (MW) of P3 on the device performances were further studied and enhanced photovoltaic parameters were achieved for the medium molecular weight P3 based device, with a corresponding open circuit voltage ( V oc ) of 0.80 V, short-circuit current density ( J sc ) of 14.7 mA cm −2, high fill factor (FF) of 71.9% and the resulting best PCE of 8.47%, verifying that P3 with an appropriate MW should be a promising polymer for highly efficient photovoltaic application.